Translation Studies Research Orientation of S1 & S2 Sinta-indexed Journal Publications - Pratiwi, Berlin Insan (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. This descriptive qualitative research examines the distribution of translation studies of Sinta-indexed journals (S1 and S2) through a dataset of 19 journals and 60 articles. The objective of this article is to offer a clear depiction of the current direction that research is taking within the field of translation. The empirical results derived from the study demonstrate a discernibly higher frequency of S2 journals in comparison to their S1 counterparts. This observed disparity can reasonably be attributed to the divergent criteria employed in the classification of these journals as well as the ongoing progress and expansion of the journal landscape. S1 journals exhibit a greater inclination toward prioritizing applied translation studies, whereas both categories demonstrate a prevailing prevalence of research centered around pure translation, thereby suggesting a possible imperative to advance the deployment of research with applied orientations. The results of this study demonstrate a prevalence of the qualitative methodology in translation studies across both S1 and S2 journals. Quantitative research is notably infrequent, constituting a minority fraction of the publications, whereas mixed-method approaches are also limited but present to some extent. Collaborative efforts are observed in S1 publications, with larger-scale projects, whereas S2 publications involve smaller, collaborative teams. Foreign researchers contribute more to S1, while S2 showcases predominantly Indonesian authors, but both display international collaboration. Thus, encouraging more applied translation research and industry collaboration can enhance the practical impact of translation studies. The above findings are significant not only for scholars engaged in translation studies but also for journal editors when making editorial judgments.Keywords: Translation Studies, Research Orientation,  Sinta 1, Sinta 2